Association of platelet-to-neutrophil ratios with 1-year outcome and mortality in patients with acute ischemic stroke. (28th February 2023) - Geng, Leiyu; Zuo, Lei; Li, Hangna; Wang, Yanjuan; Zhang, Qiao; Ran, Jing; Yan, Fuling; Zhang, Zhengsheng; Xie, Chunming
Highlights: 718 patients were included to assess the predictive value of PNR on 1-year outcome. PNR may serve as a marker for early predicting the long-term prognosis of AIS. PNR, NIHSS, RBCs and age could construct a risk model for 1-year mortality of AIS. Abstract: Background: Platelet-neutrophil crosstalk is being increasingly recognized as a driver of inflammation and thrombosis in patients with ischemic stroke. The aim of this study was to investigate the potential of PNR value in predicting the long-term prognosis and evaluate whether or not an available and routine blood cell biomarker could help predict the long-term neurological function and mortality in AIS patients. Methods: A total of 718 patients with suspected acute ischemic stroke were involved and followed up for 1 year by standard telephone interview or reexamination. Kaplan-Meier curve, Univariate and Multivariate Cox Regression were analyzed using Statistical Packages for Social Sciences. Results: ROC curve for PNR to evaluate 1-year outcomes was analyzed and the area under the curve (AUC) was 0.659 (P < 0.001). The cutoff point was observed at 38.30, with a sensitivity of 53.09 % and a specificity of 71.25 %. Moreover, patients in PNR ≤ 38.30 were more likely to have more serious NIHSS on admission, 1-year mRS and higher 1-year mortality (P < 0.001, respectively). The 1-year mortality in the low PNR group was significantly higher than that of the high PNR group (log-rank tests: P < 0.0001). Age, NIHSS, RBC and PNR were combined into model B which significantly increased the AUC value from 0.736 to 0.888 compared to model A (including Age, NIHSS and RBC). Conclusion: PNR may serve as a readily assessable biomarker for early predicting neurological deterioration and the long-term prognosis of AIS. The nomogram that included age, NIHSS, PNR and RBC may be a useful predictive tool for 1-year mortality.